2015
DOI: 10.1007/s40722-015-0015-5
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Effect of seabed slope on the pile behaviour of a fixed offshore platform under lateral forces

Abstract: Fixed offshore platforms supported by pile foundations have to resist lateral loads due to wave and current forces. The response to environmental loads is strongly affected by the soil-structure (pile) interaction. Forces exerted by waves are the predominant lateral environmental forces governing jacket structure design, especially the foundation piles. The purpose of the present investigation is to perform a static wave analysis of a typical fixed offshore platform in extreme environmental conditions and to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Based on the analytical model, a simplified evaluation method of peak response is proposed. Muthukkumaran et al [10] used the finite difference method to investigate the effect of combined lateral and vertical loads on a pile-supported platform and analyzed the effect of different seabed slopes on the soil-pile interaction behavior. The results show that the displacements at the pile top and seabed, and the depths at which maximum shear and bending moments occur, all increase as the seabed slope increases.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the analytical model, a simplified evaluation method of peak response is proposed. Muthukkumaran et al [10] used the finite difference method to investigate the effect of combined lateral and vertical loads on a pile-supported platform and analyzed the effect of different seabed slopes on the soil-pile interaction behavior. The results show that the displacements at the pile top and seabed, and the depths at which maximum shear and bending moments occur, all increase as the seabed slope increases.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the effect of applying an axial load to the pile on the produced bending moment and lateral displacement along the depth was minimal and negligible. The effect of the seabed slope on the piles' behaviour of a fixed offshore platform under lateral loads was investigated by Muthukkumaran and Arun [8]. Their results indicated that the lateral displacement at the pile tip, the seabed level, increases with the seabed slope.…”
Section: Introductionmentioning
confidence: 99%